2012
DOI: 10.17744/mehc.34.4.w35q80w11kgpqn26
|View full text |Cite
|
Sign up to set email alerts
|

How Gratitude Relates to Burnout and Job Satisfaction in Mental Health Professionals

Abstract: This study investigated how gratitude relates to burnout and job satisfaction in mental health professionals. Sixty-five mental health professionals (counselors, case managers, clinical administrators/supervisors, employment/housing specialists, social workers, psychologists) completed questionnaires assessing demographics, job context variables, hope, gratitude, burnout, and job satisfaction. Consistent with hypotheses, workplace-specific gratitude predicted emotional exhaustion, depersonalization, and job sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 53 publications
3
62
0
2
Order By: Relevance
“…These findings are similar to those of a previous study that found burnout and compassion satisfaction mediated the relationship between personal characteristics and job satisfaction (Kim et al, ). The findings are also consistent with previous studies showing that resilience is related to burnout and compassion satisfaction (Rushton et al, ), and gratitude disposition to burnout (Lanham et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings are similar to those of a previous study that found burnout and compassion satisfaction mediated the relationship between personal characteristics and job satisfaction (Kim et al, ). The findings are also consistent with previous studies showing that resilience is related to burnout and compassion satisfaction (Rushton et al, ), and gratitude disposition to burnout (Lanham et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Gratitude disposition is related to burnout and job satisfaction (Lanham et al, 2012) in addition to well-being (McCullough et al, 2002). Although studies on gratitude disposition in nurses are scarce, it has been related to job satisfaction and well-being in clinical nurses (Chong et al, 2017;Jun et al, 2015).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Caseload and income also showed both negative and positive relationships with burnout, but the strength of the relationships was weak, usually ranging from −0.20 to 0.09 (Acker, ; Wallace, Lee, & Lee, ; Wilkerson, ). Negative clientele consistently showed a positive relationship with burnout, but this result was also unreliable because some studies (Lanham et al, ) showed very weak correlations while others (Craig & Sprang, ; Thompson et al, ) showed very strong correlations with burnout symptoms.…”
Section: Introductionmentioning
confidence: 98%